System Dynamics Approach to Potable Water Management in Eastern Cape Province of South Africa - Motsi Ephrey MATLAKALA; S. T. MONA (Journal of Digital Food, Energy & Water Systems)
Large swaths of rural communities in South Africa are faced with water shortages. The Eastern Cape province is one of the most hard-hit areas in the country with very unskilled water administrators and old infrastructure exacerbating the problem. Water shortage is due to the mismanagement of resources that are meant to install, operate, and improve water infrastructures in the province. An increase in population also contributes significantly to the challenge of water shortages. Available water is not potable enough for consumption, as a result, the province is under the stress of access to potable water. The purpose of this study was to model the water supply chain and to determine the nature and causes of water delivery challenges. The model will be used as a decision-support tool to help achieve sustainable water management in the province. System dynamics is an appropriate methodology used to understand cause and effect relationships, policy decisions, and feedback and has been successfully used in solving water management problems in particular. A System dynamics model is developed using the Vensim PLE 8.0.9 (Double Precision) to determine opportunities for improvement in water management, water access, and water supply. The systems dynamics modeling is discussed herein.